Work Hours Constraints: Impacts and Policy Implications - Amelie F. Constant; Steffen Otterbach (Institute for the Study of Labor (IZA), 2011)
If individuals reveal their preference as consumers, then they are taken seriously. What happens if individuals, as employees, reveal their preferences in working hours? And what happens if there is a misalignment between actual hours worked and preferred hours, the so-called work hours constraints? How does this affect the productivity of workers, their health, and overall life satisfaction? Labor supply and corresponding demand are fundamental to production. Labor economists know for long that the fit of a worker in a job and the matching of skills to the assigned employment are of paramount importance; they guarantee high productivity, quality output, and individual happiness. Employees demand higher social awareness and a working environment where they feel useful and happy. The evidence shows that discrepancies between preferred hours of work and actual hours of work can have serious detrimental effects on workers, perverse effects on labor supply with unintended direct ramifications on the labor market and indirect implications on the goods and services markets. The sooner employers acknowledge and address working hours constraints the faster we can build work lives that make us better off.
Keywords: I10; J21; J22; 330; labor market; work time; work hours constraints; health; happiness; satisfaction; Arbeitsangebot; Arbeitszeitgestaltung; Präferenztheorie; Arbeitsproduktivität; Arbeitszufriedenheit; Zufriedenheit; Deutschland